Les configurations de l'espace économique et la crise politique en Belgique - Christian Vandermotten (EchoGéo)
Belgium's political evolution is part of a process of dissociative federalization. This can only be understood with reference to the country’s economic structures and their long-term trend. The community ideology prevailing in Flanders was developed as a reaction to the secular crisis of the Flemish economy, from the mid-19th Century to the inter-war, and to the arrogance of the French-speaking national and Flemish upper class of that time. The economic crisis that affected Wallonia and many European early coal-mining and metallurgical areas after World War II generated in Flanders the feeling that Wallonia had become a burden for its own development, characterized in turn by strong manufacturing growth. Even if a very large majority of Brussels' population is French-speaking (at least in the public sphere), working-class Wallonia took long to become aware of the importance of an economic and political solidarity with the capital, seen as “the city of capitalists”. Inversely, the Flemish Region considers Brussels as its own capital despite it doesn't like its French-speaking and cosmopolitan character. However, in the framework of globalization, Brussels appears to be the driving force behind Belgium’s tertiarized economy. As such, the capital is both a source of discord in the political life and a possible cement for Belgium. But even if Belgium survives, the federal powers will undoubtedly grow weaker.